Meat Consumption : Is our Free Choice Actually Free? - Sattar-zada, Ayla; Chytková, Zuzana; Pašmik, Jaroslav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
Meat consumption, its framing in the media and its effects on society have been of high interest to various scholars, marketing specialists and the wider public. While people seem to be knowledgeable of certain problems connected to meat consumption, it continues growing worldwide. This paper aims to investigate how a particular relationship between meat and its consumers is being created, and what influences this process. The paper grounds its conclusions on literature review, primarily focused on the phenomena of meat dissociation and media cultivation, and qualitative semiotic analysis of TV commercials aired by the U.S. most successful meat producer Tyson Foods Inc. The study shows that symbolism created around meat is closely linked to particular desired states of mind and lifestyles, while the link between meat and animals is completely absent. It further concludes that the mentioned symbolism is built upon certain gender roles and cultural characteristics present in the society. The author believes that the findings can be of interest to those who aim to re-shape the role of meat in our daily lives and focus on the promotion of more sustainable alternatives.
Vedoucí práce: Zuzana Chytková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses